أثر التدفقات المالية الدولية على التنمية الاقتصادية في الجزائر دراسة قياسية باستخدام نموذج ARDL خلال الفترة ) 1980 – 2021 ): The impact of international financial flows on economic development in Algeria An econometric study using the ARDL model during the period (1980-2021) - بن العايب عادل عبد الباسط; بودالي بلقاسم (Journal of North African Economies, 2025)
This study seeks to measure the impact of international financial flows on long-term economic development in Algeria during the period from 1980 to 2021, using an autoregressive model of lag-distributed time gaps (ARDL). The results of the study concluded that there is a long-term equilibrium relationship between international financial flows and economic development in Algeria. The estimated results revealed that international financial flows (FDI, FPI, ODA, REM) have a positive and significant impact on economic development in Algeria in the short and long time frame, with the exception of the total foreign debt stock, where a negative and significant impact on economic development in Algeria was observed.